Low velocity impact analysis of Fiber Metal Laminates (FMLs) in thermal environments with various boundary conditions. (1st August 2016) - Zarei, Hamed; Fallah, Mohadeseh; Minak, Giangiacomo; Bisadi, Hosein; Daneshmehr, AliReza
Abstract: This paper presents the dynamic response of GLARE5-3/2 subjected to low velocity impact. Governing equations are derived based on laminate theory and Hamilton's principle. The Hertzian contact law is employed to capture contact force history and other impact characteristics. A Ritz based approach appropriate for in-plane loads and various boundary conditions is developed. The nonlinear system of equations is solved using the fourth order Runge–Kutta method. The validity of the present model is demonstrated by good agreement of comparisons between its predictions and results in the literature. The effect of various parameters such as impactor velocity, impactor radius, boundary conditions and thermal environment are investigated in detail. In order to consider thermal environment effect, the temperature dependent material properties are taken into account. Boundary conditions and thermal environment affect the low velocity impact response of GLARE, hitherto not reported in the open literature.